Mentoring Guidance and Counseling Teachers in Developing Group Counseling Services to Enhance Student Self-Confidence at SMPI Al-Amin - Ani Ulfiana Latifah Ulfiana Latifah; Aisatun Nafisa; Mendy Harmoko (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to describe the mentoring process of guidance and counseling (GC) teachers in developing group guidance services to improve students’ self-confidence at SMPI Al-Amin. The mentoring process is conducted as an effort to enhance the professional competence of GC teachers in planning, implementing, and evaluating group guidance services systematically and effectively. This research employs a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation. The results indicate that mentoring significantly improves the quality of service planning, group dynamics implementation skills, and evaluation processes of group guidance services. Furthermore, students’ self-confidence shows improvement, as evidenced by increased courage in expressing opinions, higher participation in group activities, and more positive self-attitudes. Therefore, mentoring GC teachers in developing group guidance services is proven to be effective in enhancing students’ self-confidence.